Methodology of Teaching a Russian Language on the Basis of Mixed Educational Technologies in the Courses of Professional Development of Pedagogical Staff (Diversity Research: Journal of Analysis and Trends, 2023)
The article describes the methodology of teaching Russian on the basis of blended learning technologies in the professional development courses for teaching staff of higher educational institutions. The main components and principles of language teaching are also highlighted. A comparative analysis of the module "Practical foreign language" is given as well.